ANALISIS DALAM MANAJEMEN KESISWAAN : MEMBENTUK KARAKTER DAN POTENSI SISWA - M.Arinalhaq; Halizah Auliah; Sobareeyah Yaya; Hesti Kusumaningrum (PT PUSTAKA CENDEKIA GROUP, 2025)
Student management is a crucial component of the education system aimed at organizing and managing all student activities from the beginning to the end of their educational journey. This article analyzes the role of student management in shaping character and developing student potential. Through a structured and continuous approach, student management can create a conducive environment for positive character development and the optimization of student potential. Factors such as the school environment, teacher support, and additional school activities play a significant role in this process. This research uses a qualitative method with a literature review approach to gather data. The findings indicate that habituating positive behavior and creating a supportive environment are highly effective in shaping good student character and maximizing their potential.